How Psychosocial Factors Contribute to Japanese Older Adults' Initiation of Advance Care Planning Discussions: A Qualitative Study. (October 2021) - Miyashita, Jun; Kohno, Ayako; Yamamoto, Yosuke; Shimizu, Sayaka; Azuma, Teruhisa; Takada, Toshihiko; Hayashi, Michio; Fukuhara, Shunichi
Objectives: This study aimed to reveal the features of older adults' advance care planning (ACP) discussions by identifying psychosocial factors related to their discussions in Japan, where people value family-centered decision making.Methods: A qualitative study using in-depth interviews was conducted with 39 participants (aged ≥65 years) recruited from the outpatient department of a community hospital in Fukushima, Japan. Data were analyzed using the grounded theory approach.Results: Through experiences of family caregiving, participants became aware of their own feelings about the end of life. Equal relationship with family members was important for lowering the threshold for having discussions. Some participants and their families in the same generation reached agreements on ACP; however, they were willing to yield to children's decision making despite these discussions.Discussions: These findings provide insights into the psychosocial factors in relation to ACP discussions and support for the role of ACP discussions in the family-centered decision-making culture.